Multifactorial diagnostics of perceptual processes of athletes in virtual reality and on a 2 D monitor - B.I. Bespalov; S.V. Leonov; A.M. Mukhamedov; N.I. Bulaeva; I.S. Polikanova (Экспериментальная психология)
Context and relevance. One of the urgent tasks of sports psychology is to develop virtual diagnostic simulators with the inclusion of a battery of chronometric tests aimed at assessing the perceptual and motor processes of athletes and possessing a high level of reliability and validity. Objective. The purpose of this work was to develop such tests for the HTC Vive Pro virtual reality system based on the Unity gaming platform. Methods and materials. Two groups of subjects participated in the study: the main group consisted of professional hockey players, the control group consisted of students (14 people in each group). The latent time of motor reactions (RT) of the subjects at the time of the appearance of the puck on the court, BP at the beginning or in the direction of its movement, was chosen as the dependent variable. Four variables varied on two levels — the «Environment» (virtual or 2D monitor), the «Distance» from the puck to the gates, the «Direction» of their movement to the left or right side of the gates, as well as the direction to one of the two close «Zones» of gates. All the tests were initially performed on a 2D monitor, and then in a virtual environment. Results. It is shown that some test indicators have high criterion validity, i.e. they differ significantly in the group of students and hockey players, and also have significant correlation and regression relationships with professional hockey players. These differences and connections were explained by estimating and comparing the duration of perceptual and premotor processes, such as perceiving varying characteristics of puck movement and choosing the right keys to respond to these characteristics. The retest reliability of the test indicators obtained in different environments was assessed by their correlation coefficients and proved to be high for most indicators. Conclusions. This makes it possible, when developing virtual diagnostic simulators, to carry out instrumental psychodiagnostics of perceptual and motor processes of athletes not only in a virtual environment, but also "in the field" using dynamic chronometric tests run on a laptop (without a VR helmet).